PTIP-Associated Protein 1: More Than a Component of the MLL3/4 Complex - Liu, Bo; Li, Zhen (Frontiers in Genetics, 2022)
PTIP-associated protein 1 (PA1) is a unique component of MLL3/4 complexes, which are important mammalian histone 3 lysine 4 (H3K4) methyltransferases. PA1 has generated research interests due to its involvement in many essential biological processes such as adipogenesis, B cell class switch recombination, spermatogenesis, and embryonic development. Besides the classical role of PA1 in H3K4 methylation, non-classical functions have also been discovered in recent studies. In this review, we systematically summarize the expression pattern of PA1 protein in human and sort the specific molecular mechanism of PA1 in various biological processes. Meanwhile, we provide some new perspectives on the role of PA1 for future studies. A comprehensive understanding of the biological functions and molecular mechanisms of PA1 will facilitate the investigation on its complicated roles in transcriptional regulation.